EFFECTS OF CHINESE MATERIA MEDICA-FUBAO DANGGUI JIAO ON EXPERIMENTAL ENDOMETRIOSIS - Sun, Xing; Chen, Lijue; Zeng, Fanbo (African Journal of Traditional, Complementary and Alternative Medicines, 2011)
The objective of this paper was to investigate the effects of a Chinese Materia Medica variant -Fubao Danggui Jiao (FDJ)-on experimental endometriosis. An endometriosis model was created by virtue of auto-transplantation of endometrial tissue onto rats’ abdominal walls. The implants were allowed to grow for 30 days until the successful completion of the model. After that, forty endometriotic rats were randomly divided into four study groups and given different treatments: (1) negative control group (water, 2ml/kg, per os); (2) FDJ-A group (FDJ, 2ml/kg, per os); (3) FDJ-B group (FDJ, 4ml/kg, per os); (4) Danazol group (70mg/kg, per os). After 30 days with treatments, the volumes of endometriotic implants in each rat were measured. The implants and normal uterine horns were removed for routine histological examination. FDJ caused significant decreases in volumes of the surviving endometriotic implants, with two different doses having statistically equivalent effects. Upon histological examination, FDJ was observed to cause regression of epithelium and stroma of endometriotic implants. FDJ had revealed promising therapeutic effects on endometriosis.